2021
DOI: 10.14202/vetworld.2021.1-10
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of brucellosis and the brucellosis model at the individual level of dairy cattle in the West Bandung District, Indonesia

Abstract: Background and Aim: Brucellosis is a zoonotic bacterial infectious disease. West Bandung is a center for dairy farming in West Java Province District and endemic for brucellosis. The aim of the study was to determine the prevalence, the associated risk factors, and the brucellosis model at the individual level of dairy cattle in the West Bandung District. Materials and Methods: The research was conducted through a cross-sectional study. The samples were collected from the serum blood of dairy cattle. Data obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 43 publications
2
10
0
1
Order By: Relevance
“…This study found that a history of abortion was significantly associated with brucellosis seropositivity and that dairy cattle kept in a herd with a history of abortion were more likely to be brucellosis seropositive as compared with those in herds with no history of abortion (OR 4.91, 95% CI 1.43–16.9). These findings were in agreement with the findings of other studies in dairy cattle [ 11 , 41 , 42 ]. Farmers should be encouraged to report abortions in dairy cattle to the livestock officials for closer monitoring of the disease and implementation of control measures.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study found that a history of abortion was significantly associated with brucellosis seropositivity and that dairy cattle kept in a herd with a history of abortion were more likely to be brucellosis seropositive as compared with those in herds with no history of abortion (OR 4.91, 95% CI 1.43–16.9). These findings were in agreement with the findings of other studies in dairy cattle [ 11 , 41 , 42 ]. Farmers should be encouraged to report abortions in dairy cattle to the livestock officials for closer monitoring of the disease and implementation of control measures.…”
Section: Discussionsupporting
confidence: 94%
“…Bovine brucellosis causes nonspecific signs such as abortion during the last trimester, retained placenta, reduced milk production, orchitis, epididymitis, and rarely, arthritis [ 4 , 8 , 9 ]. A number of predisposing factors have been associated with brucellosis seropositivity such as older age of animal, history of abortion, large herd size, access to surface water, location, and contact with other animals [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The different timing of abortion may be due to differing etiologies. Kamrup (Metropolitan) district of Assam, for example, has been reported to have a high prevalence of brucellosis [ 15 , 29 , 30 ], and studies suggest that dairy animals that suffer from brucellosis generally abort in third trimester [ 10 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the roadmap has not been implemented optimally, so some areas still report the prevalence of brucellosis in the high category (>2%). According to Balai Veteriner Subang [ 9 ], the prevalence of brucellosis was 3.6% in West Java, 5.10% in West Bandung District [ 10 ], and 15.77% in Bandung District [ 11 ]. As a result, efforts must be made to optimize the implementation of the brucellosis eradication roadmap.…”
Section: Introductionmentioning
confidence: 99%